Site-specific phosphorylation of TRANSPARENT TESTA GLABRA1 mediates carbon partitioning in Arabidopsis seeds - Chengxiang Li (Nature Portfolio, 2018)
Seed development relies upon carbon supplied by the parent plant. Here the authors propose that in Arabidopsis, phosphorylation of TTG1 by SHAGGY-like kinases 11/12 acts to regulate carbon flow between fatty acid synthesis in the embryo and mucilage and flavonoid production in the seed coat.